Tex13a Optimizes Sperm Motility via Its Potential Roles in mRNA Turnover - Li, Yinchuan; Mi, Panpan; Chen, Xue; Wu, Jiabao; Liu, Xiaohua; Tang, Yunge; Cheng, Jinmei; Huang, Yingying; Qin, Weibing; Cheng, C. Yan; Sun, Fei (Frontiers in Cell and Developmental Biology, 2021)
During the late stages of spermiogenesis, mRNAs have been reported to undergo massive selective degradation. However, the mechanisms regulating this biological process are unknown. In this report, we have identified a spermatid-specific gene, Tex13a, which was found to be involved in the targeted degradation of mRNAs encoding certain structural components of sperm via CCR4-NOT complex. Deletion of Tex13a led to a delayed decay of these mRNAs, lowered the levels of house-keeping genes and ultimately affected several key parameters associated with the control of sperm motility.